Serum levels of glial fibrillary acidic protein in patients with amyotrophic lateral sclerosis. Issue 1 (16th December 2022) - Verde, Federico; Milone, Ilaria; Maranzano, Alessio; Colombo, Eleonora; Torre, Silvia; Solca, Federica; Doretti, Alberto; Gentile, Francesco; Manini, Arianna; Bonetti, Ruggero; Peverelli, Silvia; Messina, Stefano; et al.
Abstract: Objective: To compare serum levels of the astrocyte biomarker glial fibrillary acidic protein (GFAP) in patients with amyotrophic lateral sclerosis (ALS) and neurologically healthy controls and to analyze the relations between serum GFAP (sGFAP) and phenotype in ALS. Methods: We studied 114 ALS patients and 38 controls. sGFAP was quantified with single molecule array (Simoa) technology. Results: In both ALS patients and controls, sGFAP moderately correlated with age. ALS patients had higher sGFAP levels compared to controls, but this yielded a weak discriminative performance (AUC = 0.6198). In ALS, sGFAP was not associated with most of the motor phenotypic features, including site of onset, functional status, disease progression rate, disease stage, and indices of upper (UMN) and lower motor neuron (LMN) impairment. However, sGFAP negatively correlated with cognitive scores regarding ALS‐nonspecific functions, particularly memory ( r = −0.2082) and tended to be higher in ALS patients with eye movement abnormalities ( p = 0.0628). sGFAP also correlated with polysomnographic indices of oxygen desaturation (ODI; r = 0.2639) and apnea‐hypopnea (AHI; r = 0.2858). In a multivariate analysis, sGFAP was negatively associated with survival (HR = 1.005). Relevantly, we found a negative correlation between sGFAP and estimated glomerular filtration rate (eGFR; r = −0.3500). Interpretation: Our work provides neurochemical evidence of astrocyte involvement in ALS pathophysiology and particularly in the development of extra‐motor manifestations (namely, cognitive – memory – impairment) and respiratory dysfunction. The negative correlation between sGFAP and eGFR has practical relevance and should not be disregarded in future investigations.